A Selective High Performance Liquid Chromatographic Method to Follow the Hydrolytic Degradation of Nicardipine Hydrochloride - K. E. Ibrahim; R. M. Al-Ashban; L. B. Babiker (E-Journal of Chemistry)
A simple, stability indicating, reverse phase high performance liquid chromatographic method was developed and validated for determination of nicardipine hydrochloride (NC) in the presence of its degradation products. The chromatographic separation was performed on Hypersil, BDS-C18, 30 cm × 3.9 mm id, at ambient temperature with UV-detection at 254 nm. A mixture of 20% (v/v) aqueous 0.01 M sodium acetate∕acetic acid buffer (pH 4.5) and 80% acetonitrile was used as the mobile phase at a flow rate of 1.5 mL min-1, losartan was used as internal standard. The calibration curve is linear over the concentration range 5-40 μg mL-1, with a regression coefficient of 0.9984 and the % recovery was 99.78±0.17. The method was used to investigate the kinetics of alkaline, acids induced degradation, effect of buffer concentration and temperature. The degradation followed first-order kinetics. The rate constant, half-life time, and activation energy were calculated